The Issue of Values in Aesthetics of Roman Ingarden - Cichy, Barbara (Hybris, 2011)
The axiological reflection, deeply rooted in a wide philosophical issue, constitutes an extremely important point in Roman Ingarden’s considerations. In hereby article, my aim is to concentrate mainly on presenting the question of aesthetic and artistic values. This division, with a distinction between a work of art and its realization, i.e. the aesthetic object, can be treated without doubt as one of the most important achievements of Ingarden’s theory of values. One part of this thesis will refer to the conception of metaphysic qualities. The philosopher consecrates a relatively modest indifference to this problem however it does not diminish the significance and meaningful role, which these qualities play in the aesthetic system created by himself. The initial overview of basic questions of the overall theory of values concerning: typology, way of existence, form and matter of values and questions related to objectivity of values, seems to be essential.